2014
DOI: 10.1007/s10951-014-0411-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-time scheduling to minimize machine busy times

Abstract: ABSTRACT.We consider the following fundamental scheduling problem. The input consists of n jobs to be scheduled on a set of machines of bounded capacities. Each job is associated with a release time, a due date, a processing time and demand for machine capacity. The goal is to schedule all of the jobs non-preemptively in their release-time-deadline windows, subject to machine capacity constraints, such that the total busy time of the machines is minimized. Our problem has important applications in power-aware … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Thus, the results of Khandekar et al [14] and Chang, Khuller and Mukherjee [7] have direct implications for us. They show that minimizing busy time can be done efficiently for purely non-preemptive and purely preemptive instances, respectively.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Thus, the results of Khandekar et al [14] and Chang, Khuller and Mukherjee [7] have direct implications for us. They show that minimizing busy time can be done efficiently for purely non-preemptive and purely preemptive instances, respectively.…”
Section: Introductionmentioning
confidence: 85%
“…We know that both the non-preemptive and preemptive MAXCONNECTIVITY and MINCONNECTIVITY on a path are solvable in polynomial time by Theorem 1 and [14, Theorem 9], respectively. Notice that the parameter g in [14] is in our setting ∞. Interestingly, the complexity changes when mixing the two job types -even on a simple path.…”
Section: Mixed Schedulingmentioning
confidence: 98%
See 2 more Smart Citations
“…This is why we study the Flexible Job Scheduling problem, which can be seen as a special case of the generalized MinUsageTime DBP problem by assuming the bin to have an infinite capacity. Khandekar et al [45] showed that the Flexible Job Scheduling problem can be solved in polynomial time via the dynamic programming technique in the offline setting. We thus mainly focus on the problem in the online setting in this chapter.…”
Section: Chaptermentioning
confidence: 99%